Kesantunan Berbahasa pada Anak Melalui Pembiasaan - Juhaeni Juhaeni; Wahyuningtias Ludiawati; Safaruddin Safaruddin; Lisfiana Nur Laili; Lutfiatus Zahrotul Ulfa; Putri Ambarwati (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2020)
The habit of politeness in language in children aged 5-6 years is something that is crucial. This study aims to analyze the impact of using the word do not replace the word sorry for children. This study uses qualitative methods with data triangulation techniques. Samples taken were students of group A PGRA Mamba’ul Hisan Surabaya. Data collection techniques used are 1) Making observations in class A1, A2, A3, 2) Interview with class teachers, 3) Analyzing data based on theory, 4) Summing up the results obtained. The data taken consisted of 3 samples from 3 groups who were accustomed to politeness in language. The results obtained include: children can accept mistakes, children can be more polite and more polite in talking, children are accustomed to gentle reprimands.